Vidensformer i samfundsfag - Christensen, Torben Spanget; Mette Damgaard Jørgensen, Mette Damgaard Jørgensen; Wikman, Lasse (POLIS – tidsskrift for samfundsfagsdidaktik, 2021)
Vidensformer i samfundsfag